Bill O'Reilly's Legends & Lies: The Civil War - Fisher, David 1946-; O'Reilly, Bill (New York : Henry Holt and Company, 2017)
"From the birth of the Republican Party to the Confederacy's first convention, the Underground Railroad to the Emancipation Proclamation, the Battle of Gettysburg to the assassination of Abraham Lincoln, [this book examines] the often little known stories behind the battle lines of America's bloodiest war and debunks the myths that surround its greatest figures"--Amazon.com.
Includes bibliographical references and index.
Keywords: HISTORY / United States / Civil War Period (1850-1877).; HISTORY / Military / United States; United States -- History -- Civil War, 1861-1865; United States -- Miscellanea. -- History -- Civil War, 1861-1865